Retraction Note: E-Blue: Implementation of an Integrated Blue Economy Ecosystem to Increase Coastal MSMEs Competitiveness (Journal of Indonesian Economy and Business, Vol. 40, No. 2, May, 2025, 10.22146/jieb.v40i2.10994) - Perdana, Tito Aditya; Purusa, Nanda Adhi; Kurniawan, Rudi; Suryawijaya, Tito Wira Eka (Faculty of Economics and Business, Universitas Gadjah Mada, 2025)
The Journal of Indonesian Economy and Business (JIEB) announces the retraction of the article titled